2012
DOI: 10.1590/s0104-11692012000500004
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in people with chronic hemodialysis: association with sociodemographic, medical-clinical and laboratory variables

Abstract: Aim: determine the quality of life for people in chronic hemodialysis and its association with sociodemographic, medical-clinical and laboratory variables. Method: exploratory, descriptive, cross-sectional study with stratified probability sampling. Quality of life was assessed using the KDQOL-36 TM . Data were analyzed using SPSS statistical software.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
23
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 16 publications
18
23
0
8
Order By: Relevance
“…Consistent with aforementioned studies, Taheri et al suggested that long-term dialysis treatment reduces the patients' quality of life (4). Guerra et al and Santos et al observed higher mental function scores in patients on hemodialysis for less than 36 months compared to those on dialysis for more than 3 years (28,29). It was believed that an increase in duration of hemodialysis might cause the patients being adapted to hemodialysis and improvement of uremic symptoms to enhance their quality of life (17).…”
Section: Discussionmentioning
confidence: 94%
“…Consistent with aforementioned studies, Taheri et al suggested that long-term dialysis treatment reduces the patients' quality of life (4). Guerra et al and Santos et al observed higher mental function scores in patients on hemodialysis for less than 36 months compared to those on dialysis for more than 3 years (28,29). It was believed that an increase in duration of hemodialysis might cause the patients being adapted to hemodialysis and improvement of uremic symptoms to enhance their quality of life (17).…”
Section: Discussionmentioning
confidence: 94%
“…[6][7] Even though renal replacement therapies promote the maintenance and prolongation of life, they do not cure the disease and even harm one's daily life and QOL in the long run. 8 Patients undergoing hemodialysis face limitations in their daily lives and also experience many losses and biopsychosocial changes, such as the loss of health (at a physiological and biochemical level), anemia, loss of physical, cognitive and sexual capacity, loss of the capacity to work and to perform other tasks and functions, and dependency on medical treatment and renal therapy, in addition to physical changes and body image, and diet and fluid restrictions associated with the treatment. 9 Therefore, those living with CKD must adapt not only to the disease and its treatment, but also to the physiological, psychosocial and spiritual problems arising from this process, 10 which are situations that directly impact patients' QOL.…”
Section: Introductionmentioning
confidence: 99%
“…Other losses, such as the loss of functional capacity and financial losses (Guerra-Guerrero, Sanhueza-Alvarado, & CaceresEspina, 2012;Lopes et al, 2014;Silva et al, 2014), become even more prominent when family support is lacking (Terra et al, 2010).…”
Section: Viviane Gregoleti Universidade De Passo Fundo Passo Fundo-rmentioning
confidence: 99%